The Performance of Cold-Formed Steel Members with Stiffened Perforations - Nasam Khater; MAHMOUD EL-BOGHDADI; Nashwa Yossef (Journal of Engineering Research - Egypt)
CFS sections are usually supplied with openings to adapt construction services. Nevertheless, the area lowering in the web influences their strengths. If stiffeners are provided near the web openings, the reduction in flexural capacity could be recovered. Therefore, this paper introduces a study on the CFS section with stiffened perforations. A finite element (FE) analysis was accomplished. The numerical model was verified versus experimental and numerical tests from prior research and then utilized in performing parametric studies. The influence of circular openings with various sizes and various stiffener lengths on the flexural capacity was examined in the nonlinear analysis. Depending on the findings of the study, it has been determined that the introduction of stiffened openings into the CFS members will result in the restoration of the original flexural capacity.